Illness Risk Representation beliefs underlying adolescents' cardiovascular disease risk appraisals and the preventative role of physical activity. Issue 1 (9th December 2019) - Newby, Katie; Varnes, Laura; Yorke, Eleanor; Meisel, Susanne F.; Fisher, Abi
Abstract : Objectives: The primary aim was to explore adolescents' cardiovascular disease risk appraisals and establish whether they understood the preventative role of physical activity (PA). The secondary aim was to examine whether adolescents' cardiovascular disease risk appraisal fitted with the Illness Risk Representations (IRR) framework. Design: Qualitative. Methods: Thirty‐one adolescents aged between 13 and 15 years participated in semi‐structured interviews. Data were analysed using Framework Analysis. Results: Knowledge of lifestyle behaviours contributing to cardiovascular disease was good. Participants reflected on their current (or expected future) patterns of these behaviours when making judgements about lifetime risk. They struggled however to explain how different health behaviours, including PA, affected the development of the disease. Cardiovascular disease was viewed as potentially fatal, but participants had only a superficial understanding of the consequences of, or treatments for, the disease. The IRR framework, as proposed by Cameron (2003, https://cancercontrol.cancer.gov/brp/research/theories_project/cameron.pdf ), largely captured the way in which adolescents' made judgements about their risk of cardiovascular disease. Conclusions: The findings suggest that adolescents are underestimating their risk of cardiovascular disease due to unhelpful beliefs. Interventions should: provide clear and simple explanations of how different health behaviours contribute to cardiovascular risk, highlight discrepancies that exist between current levels of preventative behaviour and that required to confer a protective effect, expose the false belief that a lack of PA in early life can be compensated for in later adulthood, and aid understanding of the true impact that the disease and its treatment could have of health and quality of life outcomes. Statement of contribution What is already known on this subject? Physical activity (PA) throughout one's lifetime can reduce the risk of developing cardiovascular disease. The majority of adolescents' do not meet the recommended levels of PA. Changing beliefs about the risk of cardiovascular disease might be a useful strategy to motivate engagement in PA. What does this study add? An increased understanding of adolescents' knowledge of cardiovascular disease and the link with PA. Identification of strategies to change adolescents' risk perceptions of cardiovascular disease in ways that could motivate PA. Evidence to support the Illness Risk Representation framework.